The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/jom.0000000000000676
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and the Risk of Birth Defects in Anqing City, China

Abstract: The results suggested that exposure to ambient SO2 during pregnancy may increase the risk of birth defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Conversely, they differed from those obtained by Dadvand et al [ 32 ], which showed an inverse relationship between maternal exposure to SO 2 and risk of ventricular septal defect similarly to Strickland et al [ 23 ] and Hansen et al [ 24 ]. More recently, the association between the exposure to ambient SO 2 during pregnancy and an increase in birth risk defects has been confirmed in a retrospective study conducted in Anqing city of Eastern China [ 39 ].…”
Section: Air Pollutant Exposure and Chd Risk: Epidemiological Evidmentioning
confidence: 93%
“…Conversely, they differed from those obtained by Dadvand et al [ 32 ], which showed an inverse relationship between maternal exposure to SO 2 and risk of ventricular septal defect similarly to Strickland et al [ 23 ] and Hansen et al [ 24 ]. More recently, the association between the exposure to ambient SO 2 during pregnancy and an increase in birth risk defects has been confirmed in a retrospective study conducted in Anqing city of Eastern China [ 39 ].…”
Section: Air Pollutant Exposure and Chd Risk: Epidemiological Evidmentioning
confidence: 93%
“…[13] The retrospective cohort study in Anqing city, Eastern China, suggested that exposure to ambient sulfur dioxide (SO 2 ) during pregnancy may increase the risk of birth defects. [12] The study in Lanzhou, China, investigated a cohort of 8969 singleton live births by using inverse distance weighting way for exposure assessment found positive associations for congenital malformations of cardiac septa with PM 10 exposures in the second trimester and the entire pregnancy, and SO 2 exposures in the entire pregnancy. [11] In a word, there were differences in the studies in the selection of subgroups of birth defects, exposure window, exposure assessment method and adjustments for confounding factors, and the representativeness problem that each study conducted in different areas.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty of the 70 studies included in the review (29%) investigated the role of urban air pollution and CHD in urban areas from sources such as traffic amd coal-fired power stations [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. These studies examined criteria pollutants such as NO 2 , SO 2 , CO, O 3 , PM2.5 and PM10 measured from fixed monitoring stations.…”
Section: Urban Air Pollutionmentioning
confidence: 99%
“…All the studies represented case control studies and assigned exposure to the vulnerable window of cardiogenesis between the 3rd and 5th week post conception [103]. Generally, CO was associated with septal defects, pulmonary valve stenosis or pulmonary artery stenosis [83,88] but other studies reported inverse associations between CO and ventricular septal and conotruncal defects [84]; NO 2 was associated with coarctation of aorta, pulmonary valve stenosis and patent ductus arteriosus [92,93,99,102] but others found no associations with CHD [96]; SO 2 was associated with aortic valve stenosis, septal defects, CHD [91,96,99] and others found no associations with CHD and its subtypes [85,88]; O 3 was associated with pulmonary valve stenosis, pulmonary artery stenosis, patent ductus arteriosus and septal defects [84,94] and no associations were found with CHD in other studies [86,87,100]; PM10 was associated with patent ductus arteriosus, pulmonary valve stenosis, ventricular septal defects, transposition of the great arteries, multiple CHD, tetralogy of Fallot [84,89,90,94,98,99] whilst other studies found no associations with CHD [83,[95][96][97]; PM2.5 was associated with transposition of the great arteries, hypoplastic left heart syndrome and ventricular septal defects [90,93,97] and others found no associations [89,100]. One study by Stingone et al examined multipollutant exposures from urban air pollutants and found associations with left ventricular outflow tract obstruction…”
Section: Urban Air Pollutionmentioning
confidence: 99%